Precise localisation of 3p25 breakpoints in four patients with the 3p-syndrome. Issue 10 (October 1996) - Drumheller, T; McGillivray, B C; Behrner, D; MacLeod, P; McFadden, D E; Roberson, J; Venditti, C; Chorney, K; Chorney, M; Smith, D I
Abstract : In patients with the 3p-syndrome, hemizygous deletion of 3p25-pter is associated with profound growth failure, characteristic facial features, and mental retardation. We performed a molecular genetic analysis of 3p25 breakpoints in four patients with the 3p- syndrome, and a fifth patient with a more complex abnormality, 46, XY, der(3)t(3;?)(p25.3;?). EBV transformed lymphoblasts from each of the patients were initially characterised using fluorescent in situ hybridisation (FISH) and polymorphic microsatellite analyses. The 3p-chromosome from each patient was isolated from the normal chromosome 3 in somatic cell hybrid lines and subsequently analysed with polymorphic and monomorphic PCR amplifiable markers from 3p25. The analysis clearly shows that all five breakpoints are distinct. Furthermore, we have identified yeast artificial chromosomes that cross the 3p25 breakpoints of all four 3p-patients. Two of the patients were deleted for the von Hippel-Lindau (VHL) tumour suppressor gene, although neither has yet developed evidence of VHL disease. The patient with the most centromeric breakpoint, between D3S1585 and D3S1263, had the most severe clinical phenotype including an endocardial cushion defect that was not observed in any of the four patients who had more telomeric breakpoints. This study should provide useful insights into critical regions within 3p25 that are involved in normal human growth and development.